PENGARUH METODE FREE EXPRESSION TERHADAP KREATIVITAS SISWA MEMBUAT KARYA REKLAME PADA SISWA KELAS VI SD - Fahrul Idris Pakpahan; Putra Afriadi; Edizal Hatmi; Tri Wahyu Purnomo; Sri Mustika Aulia (Jurnal Keluarga Sehat Sejahtera, 2025)
This study is based on the low creativity of grade VI students of SD Negeri 105297 Helvetia on advertising material in the subject of Arts, Culture and Crafts. This problem is also supported by the lack of use of interesting learning methods in advertising learning. This study uses the free expression method as a solution to emphasize imaginative and active learning and is centered on students who are oriented towards developing competencies to improve student creativity. This study is a quasi-experimental study. The population of this study were all grade VI-C students of SD Negeri 105297 Helvetia with a research sample of 22 students taken from one class. This study used a creativity test instrument. Data were analyzed by normality test, homogeneity test and hypothesis test. The results of this study indicate that there is a significant effect of the use of the free expression method on students' creativity in arts and crafts on advertising material. This is based on the results of the hypothesis test with the Paired Sample T-Test test obtained a significance value of 0.000 <0.05, so it can be said that H0 is rejected and Ha is accepted.